American georgics : writings on farming, culture, and the land - Hagenstein, Edwin C.; Gregg, Sara M.; Donahue, Brian, 1955- (Yale agrarian studies., 2011)
From Thomas Jeffersons Monticello to Michelle Obamas White House organic garden, the image of America as a nation of farmers has persisted from the beginnings of the American experiment. In this rich and evocative collection of agrarian writing from the past two centuries, writers from Hector St. Jean de Crevecoeur to Wendell Berry reveal not only the great reach and durability of the American agrarian ideal, but also the ways in which society has contested and confronted its relationship to agriculture over the course of generations. Drawing inspiration from Virgils agrarian epic poem, Georgics this collection presents a complex historical portrait of the American character through its relationship to the land. From the first European settlers eager to cultivate new soil, to the Transcendentalist, utopian, and religious thinkers of the nineteenth century, American society has drawn upon the vision of a pure rural life for inspiration. Back-to-the-land movements have surged and retreated in the past centuries yet provided the agrarian roots for the environmental movement of the past forty years. Interpretative essays and a sprinkling of illustrations accompany excerpts from each of these periods of American agrarian thought, providing a framework for understanding the sweeping changes that have confronted the nations landscape.